Analisis Penerapan Akuntansi Lingkungan Pada Rumah Sakit Umum Daerah (Rsud) Panyabungan Kabupaten Mandailing Natal - Vidya Chalista; Nurlaila Nurlaila; Budi Dharma (Journal Economic Excellence Ibnu Sina, 2023)
This research is a qualitative descriptive method conducted at the Regional General Hospital (RSUD) Panyabungan Mandailing Natal Regency. This study aims to determine how the recording of environmental costs for waste treatment and the application of environmental accounting at the Panyabungan Regional General Hospital in 2022. The benefit of this research is to find out whether the recording of environmental costs for waste treatment and the application of environmental accounting at the Panyabungan Regional General Hospital of Mandailing Natal Regency has been implemented or not in accordance with PSAK 01. The data used is primary data derived from the results of interviews and secondary data from hospital financial reports. The results of this study are that the Panyabungan Regional General Hospital has made efforts in recording environmental costs and also in implementing environmental accounting. In recording environmental costs according to Hansen and Mowen's theory, Panyabungan Regional General Hospital has not met the appropriate standards because there are no prevention costs in environmental costs or in the sense that there are no activities that require prevention costs. Furthermore, environmental accounting at the Panyabungan Regional General Hospital has not been applied as a whole based on PSAK. Because the allocation of environmental costs carried out by the Panyabungan Regional General Hospital is not in accordance with PSAK No. 1 in the presentation of its financial statements. This can be seen in the presentation section of the financial statements where environmental costs are not presented specifically but in general and disclosure is not disclosed information about environmental cost accounting in the Notes to Financial Statements (CALK) of RSUD Panyabungan.